Strategies to Enhance The Resilience and Service Performance of Frontline Employees of PT Bank XYZ Makassar Regional Office - Fauzi, Humam; Baga, Lukman M.; Taryana, Asep (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The Covid-19 pandemic has brought many changes to the business world and the Indonesian economy. Corporate resilience is essential for business continuity and recovery amid such a crisis. This study aims to analyze the effect of a high-performance work system (HPWS) on employee resilience and service performance at Bank XYZ Makassar Regional Office and determine the right strategy to improve employee resilience and service performance. An online survey was conducted among 336 frontline employees of Bank XYZ Makassar Regional Office, and the data were processed using the SEM-PLS method to determine the effect between variables. The results showed that the HPWS variable had a positive and significant effect on Employee Resilience. Employee Resilience has a positive and significant effect on Employee Service Performance. HPWS directly or indirectly has a positive and significant effect on the variables of Employee Resilience and Employee Service Performance. To improve Employee resilience and Service Performance, the company's employees must re-planning the HR planning system and re-designing the workflow of frontline employees. Keywords: bank, employee resilience, employee service performance, frontliner, high-performance work system (HPWS)